Fenomena Tradisi Larangan Perkawinan Adat Mangku Dalan dan Temu Pojok Pada Masyarakat Desa Tenggulun Kecamatan Solokuro Kabupaten Lamongan - Uzlah Wahidah; Janeko (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
In reality, the customary rules of marriage between one indigenous people are different from other indigenous peoples, between one tribe is different from another, between those who are Muslim are different from those of other religions, as well as there are differences in marriage customs between urban and rural communities. other. Customs that have become a customary law will be more difficult and stronger because violations of them will meet with a sanction in accordance with the regulations that apply and are obeyed in that society. Including the custom followed by the people of Tenggulun Village, Solokuro District, Lamongan Regency where there is a prohibition on marriage caused by mangku dalan and temu corner when it is not complied with, then in the future the family will experience bad luck in the household. The results of the study found that customs in marriage in the form of prohibitions on mangku dalan customary marriages and corner gatherings carried out by the people of Tenggulun Village, Solokuro District, Lamongan Regency according to 'urf are included in 'urf shahih because they are considered not to conflict with syara law'. Meanwhile, according to Islamic law and Law No. 1 of 1974 there are no prohibitions like the above, and the public's reason for these prohibitions is only to get safety, good luck, and blessings from Allah SWT.